50 GFlops molecular dynamics on the Connection Machine 5 - Lomdahl, P. S.; Tamayo, P.; Grønbech-Jensen, N.; Beazley, D. M. (Proceedings of the 1993 ACM/IEEE conference on Supercomputing, 1993)
The authors present timings and performances numbers for a new short range three dimensional (3-D) molecular dynamics (MD) code, SPaSM, on the Connection Machine-5 (CM-5). They demonstrate that runs with more than 10/sup 8/ particles are now possible on massively parallel MIMD computers. To the best of their knowledge this is at least an order of magnitude more particles than what was previously been reported. Typical production runs show sustained performance (including communication) in the range of 47-50 GFlops on a 1024 node CM-5 with vector units (VUs). The speed of the code scales linearly with the number of processors and with the number of particles and shows 95% parallel efficiency in the speedup.